The presence of Estrada-Peña, Venzal & González-Acuña, 2003 (Acari: Argasidae) in Argentina - Venzal, José M. (2014)
Forty-two larvae of Argas keiransi (Acari: Argasidae) were collected from the Chimango Caracara, Milvago chimango (Falconiformes: Falconidae), at three localities in La Pampa Province, Argentina. Ticks were determined by a combination of palpal segment IV as long as or longer than the other palpal segments, absence of a trumpet-shaped sensillum extending from the capsule of Haller´s organ into the lumen of the tarsus, length of dorsal plate between 180 and 240 μm, length of hypostome between 180 and 205 μm, dental formula 2/2 in the basal third, 2/2 or 3/3 apically, and length of posterolateral setae between 45 and 50 μm. Morphological determination was confirmed by analysis of sequences of the mitochondrial 16S rRNA gene. The results of this work constitute the first Argentinean record of A. keiransi, which has previously been reported only from Chile.